WHICH BUSINESS INDUSTRIES WILL SURVIVE IN THE NEXT ECONOMIC CRISIS? - Khurshid Rustamov; Khusamutdinov Salokhiddin; Jamolov Dilshodbek (Web of Journals Publishing, 2024)
The research explores that which business industries will survive in the future economic crisis. Three world crisis that happened within 100 years the Great Depression, the second World War and the Great Recession help the study to identify stronger business sector. Different crisis provided various difficulties and challenges for businesses and most of them could not survive even the whole industries stopped to operate for a while. However, there is a stronger industry which always gets out of crisis with better financial statistics. Radio-electronics in the Great Depression and World War2 and electronic manufacturing in the Great Recession suffered less than other sectors. The research shows that electronics manufacturing industry will be one of survival sphere in the next world recession.
Keywords: the Great Depression, survival rate, the Great Recession, industries, crisis.